Internationalization of Brazilian franchise chains: a comparative study - Pedro Lucas de Resende Melo; Felipe Mendes Borini; Moacir de Miranda Oliveira Junior; Ronaldo Couto Parente (RAE: Revista de Administração de Empresas, 2015)
The primary goal of this paper is to comprehend the fundamental organizational differences between Brazilian franchise chains that only operate in the home market and Brazilian franchise chains that operate internationally. The sample chosen for this study comprehends 96 Brazilian franchises operating in the home market and 67 franchises with international operations; logistic regression was used to analyze data obtained from these sources. Our findings suggest that the development of a brand in international operations can be strategic for certain Brazilian franchise chains; this seems to be, however, a scarce resource for many franchises and it could be developed through international operations. With regard to the fees charged, the outcomes demonstrate that Brazilian franchises with international operations tend to charge lower fees from its franchisees to install new units. Regarding the monitoring and control of franchises, there is evidence that the monitoring capability is one of the determining factors in the development of Brazilian franchises international operations.